2021
DOI: 10.1016/j.radonc.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy for the prevention of acute radiation dermatitis in head and neck cancer patients (DERMISHEAD trial)

Abstract: Background and purpose: The purpose of this study was to investigate the effectiveness of photobiomodulation therapy (PBMT) for the prevention of acute radiation dermatitis (ARD) in head and neck cancer (HNC) patients. Materials and methods: A randomised, placebo-controlled trial (RCT) with 46 HNC patients who underwent radiotherapy (RT) with or without concomitant chemotherapy was set up (DERMISHEAD trial). Patients were randomised to receive PBM or placebo treatments from the first day of RT (2Â/week) alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Literature has shown effectiveness to mitigate radiodermatitis grade in breast cancer [28]. Robijins et al [29] demonstrated that PBM can prevent acute radiodermatitis in patients with breast cancer submitted to RT. Additionally, that study, demonstrated that 12% of the patients in the treatment group had radiodermatitis grade 2, while 44.4% of the patients in the control group had radiodermatitis grade 2 or greater grades, concluding that the severity of skin reactions were significantly less in the group which PBM was performed, which means that this is an effective tool for preventing acute radiodermatitis, thus improving the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown effectiveness to mitigate radiodermatitis grade in breast cancer [28]. Robijins et al [29] demonstrated that PBM can prevent acute radiodermatitis in patients with breast cancer submitted to RT. Additionally, that study, demonstrated that 12% of the patients in the treatment group had radiodermatitis grade 2, while 44.4% of the patients in the control group had radiodermatitis grade 2 or greater grades, concluding that the severity of skin reactions were significantly less in the group which PBM was performed, which means that this is an effective tool for preventing acute radiodermatitis, thus improving the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 A recent clinical trial (DERMISHEAD trial) performed with 46 participants with head and neck cancer patients undergoing RT, controlled by the application of a placebo laser, demonstrated a significant reduction in severe RD (RTOG ≥ 2) in the group receiving MLS® laser (25 W + 1.1 W, 808 + 905 nm, 168 mW/cm 2 , 4 J/cm 2 , twice a week). 41 There is a wide variation in the parameters of application and treatment; however, current evidence shows that PBMT in the red or near-infrared spectrum (630-905 nm) is safe and efficient in the management of various complications of oncological therapy and can be applied throughout radiotherapy and/or up to 30 days after. 22,26,42 A correct choice of dosimetry is crucial for the efficacy of this therapy and is determined by radiation parameters, which include the wavelength, power, fluence or energy density, and pulse structure, and treatment parameters, which include the dose or energy per point, time, treatment schedule, and anatomic site.…”
Section: Discussionmentioning
confidence: 99%
“…The final output would be one of the four RD categories: Grade 0, Grade 1, Grade 2, and Above Grade 2. For further analysis and discussion, Grade 0 and Grade 1 were grouped as "mild" cases, and Grade 2 and above Grade 2 were grouped as "severe" cases 24 . According to the photo-taken directions, all images were divided into two subgroups, front view and side view (left and right views).…”
Section: B Study Designmentioning
confidence: 99%